Are they paying attention? Students' lack of motivation and attention potentially threaten the utility of course evaluations. Issue 3 (3rd April 2017) - Bassett, Jonathan; Cleveland, Amanda; Acorn, Deborah; Nix, Marie; Snyder, Timothy
Abstract : Student evaluations are a common source of information used by instructors and administrators, but their utility depends on students' motivation and attention. This paper presents evidence from two studies indicating that insufficient effort responding and lack of motivation may be problems in course evaluations. In the first study, approximately one in four students responded in an improbable way to 'catch items' embedded in actual course evaluation instruments, suggesting a lack of attention. In the second study, students' responses to an online survey indicated that they doubted that their responses to course evaluations would be used by instructors or administrators. The majority of students admitted to only occasionally putting sufficient effort into their responses. Potential means for identifying insufficient effort responding and mechanisms for increasing student attention and motivation during the course evaluation process are discussed.